Okay, I'll take part a, then you can try b..
a. y = 3x - 5
If a line L is perpendicular to M, then the slope of M * slope of L = -1
So first we need to find the slope of our line, y = 3x - 5.
The general equation of a line is expressed as y = mx + c where m is the slope, and c is some constant. So in our case c = -5, and m = 3.
So the slope of the line a = 3.
Now for a slope to be perpendicular,
slope of a*slope of new line = -1.
3 * slope of new line = -1
slope of new line = -1/3.
So the slope of the perpendicular line is -1/3.
The method for b is the same...